Students’ acceptance of university institutions - Calvo de Mora, Javier; Gallego-Arrufat, María-Jesús; Lamas, Francisco-J.; García-López, Pedro-Antonio (Education Policy Analysis Archives, 2015)
This study analyzes students’ perception of university institutions. According to empirical evidence obtained from a questionnaire on perception of university institutions performed at the University of Granada, Spain, university students show perceived acceptance that is institutional, academic, and personal. Students’ perceptions contain attitudes involving a certain institutional conformity and adopt forms close to academic pragmatism. The university students surveyed, who are from different undergraduate degree programs and differ in gender and age, show a general attitude of conformity toward higher education institutions, their instructional practice, and their resources, as well as a feeling of belonging to the institution based on internal and external motivations within the higher education institution itself.